Socio-economic status and challenges of indigenous sheep production in poorly resourced Southern African development communities, pathway towards poverty alleviation and food security: a review - Ngcobo, Jabulani Nkululeko; Sithole, Sindisiwe Mbali; Mlambo, Thandiwe Patricia; Nephawe, Khathutshelo Agree (Frontiers in Animal Science, 2026)
The Southern African Development Community region is home to various indigenous sheep breeds essential to communal farmers. In contrast to the high-yielding exotic breeds preferred by commercial farmers, indigenous sheep play a vital role in the socioeconomic status of rural areas, especially those that rely on subsistence farming. Among their contributions, indigenous breeds support the food system, improve nutrition, and enhance food security, thus contributing to the Sustainable Development Goals related to food security and poverty alleviation. These sheep possess characteristics that allow them to thrive in natural habitats and are known for their resilience and low maintenance requirements, thrive on limited available forage, require minimal veterinary care, and exhibit a high level of disease resistance. However, smallholder farmers may encounter challenges when trying to access formal markets due to limited market access, making it more difficult to reap the full benefits of raising sheep. It has been reported that these sheep are endangered, and their population continues to decline, with the effective population size remaining unknown in various Southern African Development Community countries. Therefore, this comprehensive review aims to address the socio-economic status and challenges of selected Southern African Development Communities rearing indigenous sheep breeds in poorly resourced communities and their impact on responding to improving the status quo of their communities through sheep farming, thus proving pathways towards food security and poverty alleviation. This review found that preserving genetic diversity and guaranteeing long-term sustainability of livestock resources depends on the protection of indigenous sheep breeds in the whole Southern African Development Community region. Moreover, as much as research and development initiatives concentrate on increasing indigenous breeds’ production, they should also maintain their distinctive characteristics and adaptability. Furthermore, interventions should focus on overcoming barriers, including market access and veterinary care, as well as the socioeconomic development of programs that assist rural sheep farmers. This is necessary for the gap recognition between indigenous sheep breeds and socioeconomic well-being.